Early assessment of neuro-rehabilitation technology: a case study. (1st September 2010) - Petroni, Silvia; Mazzoleni, Stefano; Bellelli, Stefania; Cannizzo, Sara; Palla, Ilaria; Labella, Barbara; Sterzi, Silvia; Guglielmelli, Eugenio; Turchetti, Giuseppe
A novel mechatronic platform for neuro-rehabilitation has been developed, that measures post-stroke functional recovery through whole-body isometric force measurements. An early assessment of the prototype is here presented by using a SWOT survey. The main aim of the analysis was to perform an 'in-progress' assessment of the technology, for identifying its main strengths and limitations in order to successfully manage its introduction on the market. Even though some technical limitations emerged, an overall acceptance of the proposed approach was shown. The data collected gave useful information for bringing technical adjustments to the device and gave indications about its market potential.